Effect of shoot parameters on cracking in vegetated soil. Issue 2 (20th December 2017) - Gadi, Vinay Kumar; Bordoloi, Sanandam; Garg, Ankit; Sahoo, Lingaraj; Berretta, Christian; Sekharan, Sreedeep
Abstract : The relationship of shoot parameters, which play a major role in transpiration, with the cracking of soil has rarely been investigated. Such relation helps to analyse water use efficiency accurately. This study investigated the effect of vegetation (cowpea) age on crack formation and explored any correlation between age and cracking. The age of vegetation was expressed in the form of shoot parameters (shoot length (SL) and leaf area index (LAI)). Crack formation was expressed in the form of crack intensity factor (CIF). Ten experimental test pots were used to observe crack formation on vegetated and bare soil in a greenhouse. Image analysis in the experimental pots revealed that under drying–wetting cycles, the CIF of vegetated soil increased compared with that of bare soil. There was an evident increase in CIF with SL growth, up to a threshold length (400 mm), where lateral branch growth starts forming. There was no observable increase in CIF, with further SL growth (with negligible lateral branch formation). CIF increased with LAI up to a certain threshold value (0·56), after which the CIF was relatively the same. Two correlations have been identified for shoot parameters (SL, LAI) with the CIF for the selected species.